The application of the physiologically equivalent temperature to determine impacts of locally defined extreme heat events within vulnerable dwellings during the 2020 summer in Ankara. (June 2022) - Nouri, A. Santos; Charalampopoulos, I.; Matzarakis, A.
Highlights: PET proved more effective to quantify indoor/outdoor heat stress relationship. New extreme heat event thresholds proved critical to identify thermal stress exposure. Forced convective cooling alone improved indoor thermal stress levels. Cause-and-effect patterns between indoor/outdoor heat stress identified via PET. Abstract: This study addresses the limited work related to Heat Stress (HS) vulnerability within indoor/outdoor contexts and its relationship with local Extreme Heat Events (EHEs). Centred upon Ankara, the study focuses on building upon its weaker approach to human thermophysiological vulnerabilities in an era of climate change, and unregulated urban densification. Through newly defined local EHEs, the physiologically equivalent temperature (PET) (and its cumulative derivatives), were utilised to develop the limited approaches that utilise Energy Based Models in the scope of EHE risk management. The study was undertaken by processing hourly data from 2008 to 2020 from Ankara's Meteorological Station, and Esenboga Meteorological Station. At a finer 10 min resolution, an interior Kestrel Heat-stress Station was used to assess summer thermal conditions in 2020 within a thermally vulnerable, yet still very frequent, residential Turkish construction typology. Among other outcomes, the results indicated the permanency of indoor PET that remained above 27 °C during non EHE periods. In the case of a Very Hot Day (VHD33 ), PET remained between 29 and 32.9 °C for almost 24 h. The thermal index also indicated how forced convective cooling led to indoor reductions of PET by 3–4 K, and in duration of such HS levels to less than 2 h. Graphical abstract: Image, graphical abstract